Synonyms in Medical Terminology: Confusion for Inexperienced Translators? - Kujawska-Lis, Ewa (Papers in Linguistics, 2019)
English-language medical terminology can be occasionally confusing for translators as simultaneously both English-based and Latin-based (sometimes Greek-based) terms referring to the same disease are used. Additionally, synonymous English terms relating to the same phenomena can be employed. This may be potentially challenging, especially for inexperienced translators who are not sure which term should be selected in particular contexts. Such situations can be illustrated by the synonymous co-occurring and coexisting in relation to disorders and diseases, tumour and neoplasm, and cancer and neoplastic disease. Examining terminology mainly from the area of cardiology and nephrology, I would like to indicate that depending on various factors and the translator’s skopos, different terminology can be applied and also draw attention to the fact that medical language, like any natural language, develops; hence the change in terminology and preferences for specific terms.